Organizational Justice and Employees’ Job Commitment in Beloxxi Industries Limited Agbara, Ogun State, Nigeria. - Sholesi, Olayinka Yusuf; Olushola, Adeniyi Adeshina (The Journal of Accounting and Management, 2022)
Employees' job dedication has been negatively impacted by a steady rise in organizational unfairness. Employee engagement to Beloxxi Industries Limited was assessed in this study in light of organizational fairness. To get a sense of what people thought, the researchers used a descriptive research design and a random sampling approach. Two hundred and four of the two hundred and forty-eight questionnaires that Beloxxi industries Limited sent out were properly filled out. Using SPSS (21.0) and regression and factorial analysis, we investigated five hypotheses in this study. The study found that employees are more likely to stay in their jobs if they feel they are treated fairly in the workplace. According to the findings of the study, there is a 45.1 percent correlation between the three organizational justice components (distributive, process and interactional justice) and employee work commitment. However, it was shown that the most important factor affecting employees' dedication to their jobs is distributive justice. Employers should implement a fair method for determining employment decisions, as well as appropriate resource allocation and transparent communication, according to the study's recommendations.